EFFECTS OF TERMITE INFESTATION ON SOIL PHYSIO – CHEMICAL PROPERTIES IN SEMI – ARID TROPICS - Abdallah, Y.; Jibrin, M.; Ibrahim, I.I.; Tijjani, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The research was carried out to determine the effect of termite infestation on physio-chemical properties of soil at Futuk, in Alkaleri L.G A of Bauchi state which lies between latitude 9.30 and 12.30 N of the Equator and longitudes 8.30 and 11.080 E of the Greenwich Meridian. Stratified random sampling technique was used to collect a total of twenty-five surface (0 – 15cm) soil samples from termites infested soil and a total of nine sample from termites infested sub-soil surface (35 – 50cm). Another twenty-five samples were obtained from surface soil and nine from sub-surface of non-termite infested area, making a total of sixty-eight soils samples covering both termites infested and non-infested areas. Standard procedure was followed in the laboratory for physio-chemical properties analysis of the soil. Data collected were analysed using descriptive statistics with simple percentage. The result indicates that, the organic matter content of the termite infested soils ranges between very low to medium while that of soils without termite’s infestation ranges between very low and low. Particle size analysis shows that soils not infested by the activity of termites are mainly loamy sand and sand as the dominant class. The pH of the termite infested soils is higher than that found for the surrounding soils without termites’ activity. The result of the chemical analysis confirmed that, there is a higher amount of N, P, K and CEC in the termite infested soils compared to the figures observed from the soils without termites. Conclusively the activities of termites in the research area have led to an increase in organic matter content (OC), available phosphorus (AP), total nitrogen (TN), and soil PH.